Noninvasive Detection of Alpha-Amylase in Saliva Using Screen-Printed Carbon Electrodes: A Promising Biomarker for Clinical Oral Diagnostics - Reviansyah FH; Ristin AD; Rauf AA; Sepirasari PD; Alim FN; Nur Y; Takarini V; Yusuf M; Aripin D; Susilawati S; Komariah M; Alam BYCSSS (Medical Devices: Evidence and Research)
Faris Hernando Reviansyah,1,* Azzahra Delvyra Ristin,1,* Adil Abdul Rauf,2 Prisilia Dita Sepirasari,2 Fahmi Nur Alim,2 Yuspian Nur,3 Veni Takarini,4 Muhammad Yusuf,5 Dudi Aripin,6 Sri Susilawati,7 Maria Komariah,8 Boy Yoseph Cahya Sunan Sakti Syah Alam9 1Undergraduate Program, Faculty of Dentistry, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 2Undergraduate Program, Faculty of Mathematics and Natural Sciences, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 3Laboratory of Research and Development of FARMAKA TROPIS, Faculty of Pharmacy, Universitas Mulawarman, Samarinda, East Kalimantan, 75119, Indonesia; 4Department of Dental Materials and Technology, Faculty of Dentistry, Universitas Padjadjaran, Bandung, 40132, Indonesia; 5Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 6Department of Conservative Dentistry, Faculty of Dentistry, Universitas Padjadjaran, Bandung, 40132, Indonesia; 7Department of Dental Public Health, Faculty of Dentistry, Universitas Padjadjaran, Bandung, 40132, Indonesia; 8Department of Fundamental Nursing, Faculty of Nursing, Padjadjaran University, Bandung, 40132, Indonesia; 9Faculty of Geological Engineering, Universitas Padjadjaran, Jatinangor, Jawa Barat, 45363, Indonesia*These authors contributed equally to this workCorrespondence: Faris Hernando Reviansyah, Email faris21001@mail.unpad.ac.idBackground: Biomarkers are essential tools for diagnosing diseases. Saliva, as a human fluid, effectively reflects the body’s condition due to its rich composition. Analyzing saliva components allows for noninvasive, cost-effective, and time-efficient screening and diagnosis. Alpha-amylase, a key biomarker present in saliva, has been linked to oral diseases. This study introduces an innovative method for the noninvasive detection of alpha-amylase using screen-printed electrodes (SPEs), enabling easy and efficient screening and diagnosis.Methods: The proposed method involves measuring varying concentrations of alpha-amylase using Cyclic Voltammetry (CV) and Differential Pulse Voltammetry (DPV). Saliva samples are applied directly onto electrodes pre-coated with biomarkers and a conditioning agent, allowing for precise detection and analysis.Results: The screen-printed carbon electrode demonstrated excellent performance in detecting alpha-amylase, with clear voltammogram results, achieving a limit of detection (LOD) of 104.252 units and a limit of quantification (LOQ) of 315.915 units.Conclusion: A gold nanoparticle-modified screen-printed electrode (SPE) was developed to measure alpha-amylase quantitatively. Despite sensitivity to external interference, notably temperature, pH, and the duration of incubation, While the sensor showed sensitivity to external factors such as pH and temperature variations, it maintained a strong linear response, reinforcing its potential for reliable diagnostics with linear regression score (R² = 0.9513) across alpha-amylase concentrations of 100– 500 units. This study underscores the sensor’s effectiveness as a non-invasive tool for early detection using saliva as a biomarker, enhancing patient comfort and compliance. However, further research is needed for medical applications.Keywords: Biomarkers, Screen-printed electrodes, Saliva, Alpha-amylase